Rice productivity and nutrient-use efficiency as influenced by nutrient management in long-term rice (Oryza sativa)-wheat (Triticum aestivum) system - Paul, T.; Bisht, P.S.; Pandey, P.C.; Barman, A.; Bhattacharjya, S.; Saha, T.; Nath, C.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2011 at G.B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to evaluate the effect of nutrient management on rice productivity and nutrient use efficiency under long–term rice–wheat cropping system. The highest grain yield (6.22 t/ha) was obtained with N180 P80 K40 + Zn + FYM which was statistically higher than all the treatments except N120 P40 K40 + Zn + FYM (6.20 t/ha) and N120 P40 K40 + FYM (6.19 t/ha). Agronomic efficiency and apparent recovery of N and P were recorded higher with treatments N120 P40 K40 + Zn + FYM (26.8, 80.3 and 65.2, 55.8) and N120 P40 K40 + FYM (26.7, 80.1 and 67.0, 54.0). In case of K, treatments N120 P40 K40 + Zn + FYM, N120 P40 K40 + FYM and N180 P80 K40 + Zn + FYM recorded higheragronomic efficiency as well as apparent recovery. Physiological efficiency of N was found to be higher with treatments N180 P80 K40 + Zn + FYM, N120 P40 K40 + Zn + FYM and N120 P40 K40 + FYM,respectively, and for P and K with treatment P40 K40. N harvest index was recorded higher with control, treatments N120 P40 and P40 K40 for P and treatments N180 P80 K40 + Zn and N120 P40 K40 + Zn for K.